Comparison of Burnout Levels in Pencak Silat Adolescent Athletes - Billa, Alya Salsha; Fitri, Mustika; Paramitha, Sandey Tantra (Physical Education, Health and Recreation Study Program, Universitas Insan Budi Utomo, Indonesia, 2023)
The study aims to analyze the level of Burnout of adolescent martial arts athletes aged 10 and 15 years. This type of research is quantitative with a comparative design. Participants in the study were 10 and 15 year old pencak silat teenage athletes totaling 40 people consisting of 27 women and 13 men. The instrument used is ABQ (Athlete Burnout Questionnaire) which has 3 items, namely: emotional-physical fatigue, reduced sense of achievement, and devaluation of sports by filling out a Likert scale. The research design uses descriptive analysis and T-test. The results showed that there was an effect of Burnout on 3 sports items in adolescent martial arts athletes aged 10 and 15 years with the value of emotional-physical fatigue Sig. 0.022 <0.05 and there is an average difference between age 10 and age 15 which is 18.47%. For the variable reduced sense of achievement the value of Sig. 0.048 <0.05 there is an average difference between ages 10 and 15 years, namely 10.36%. In sports devaluation, the Sig. 0.612 > 0.05 there is an average difference between ages 10 and 15 years, namely 22.91%. Implementation of the results of data analysis is expected to compare the level of Burnout in adolescent martial arts athletes.